2019
DOI: 10.1111/vru.12808
|View full text |Cite
|
Sign up to set email alerts
|

CT variants of the caudal vena cava in 121 small breed dogs

Abstract: Computed tomography is increasingly used as a treatment planning method in canine patients with diseases of the retroperitoneum, however, published information on normal variations in the caudal vena cava (CVC) are currently lacking. The objectives of this retrospective descriptive study were to characterize CVC variants using CT angiography in a sample of small breed dogs and localize the CVC bifurcations for each variant. Inclusion criteria were small breed dogs (weight ≤ 15) that underwent contrast‐enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In human and veterinary medicine, congenital anomalies of the IVC/CVC are increasingly recognized in asymptomatic patients due to the increased use of cross-sectional imaging technique such as CT, offering simultaneous evaluation of the vascular system and urinary tract with the aid of uroangiographic ICM ( 30 ). Although the anomalies of the vessels and ureters are often clinically silent, it is important to recognize them in order to avoid potential complication during surgery and interventional radiology procedures ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human and veterinary medicine, congenital anomalies of the IVC/CVC are increasingly recognized in asymptomatic patients due to the increased use of cross-sectional imaging technique such as CT, offering simultaneous evaluation of the vascular system and urinary tract with the aid of uroangiographic ICM ( 30 ). Although the anomalies of the vessels and ureters are often clinically silent, it is important to recognize them in order to avoid potential complication during surgery and interventional radiology procedures ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of congenital anomalies of the IVC/CVC with other malformations is reported in both human and veterinary medicine, but the incidence is still unclear because these anomalies might be often underdiagnosed. Small-breed dogs was reported that 7% of patients with malformation of CVC might present with a concomitant extrahepatic portosystemic shunt, while a left-sided circumcaval ureter was reported in association with the transposition of the CVC ( 5 , 30 , 32 ). In the present case series, the only concomitant congenital anomaly found was duplication of the spleen in one patient; however, for the authors knowledge, this anomaly has never previously been associated with IVC/CVC malformations ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multitude of possible thoracic conformations and sizes among the canine population prohibits the use of an absolute CVC size measurement, and there can be wide variability in margin definition of the CVC which may create measurement error. Recent investigations have reported characteristics of anatomic CVC variations within the canine population (Bertolini et al., 2014 ; Choi et al., 2016 ; Ryu et al., 2019 ; Schwarz et al., 2009 ; Specchi et al., 2014 ). As a result, assessment of the intrathoracic CVC is often challenging, particularly for practitioners with less experience in evaluating thoracic radiographs and non‐imaging specialists.…”
Section: Introductionmentioning
confidence: 99%
“…The CVC terminates dorso-caudally in the right cardiac atrium [8]. Based on the results of retrospective veterinary studies on domestic animals, many CVC variants have been described [9], and their presence significantly increases the risk of accompanying ureteric anomalies or portosystemic shunts (Table 1). In the case that the collateral system provides an adequate venous return, most congenital venous anomalies, including duplicated CVC (dCVC), remain silent and asymptomatic [4,10,11].…”
Section: Introductionmentioning
confidence: 99%